Association between resilience and Health-Related Quality of Life (HRQOL) among Hepatitis C patients : a study in Pahang - Ummu Afeera Zainulabid
Hepatitis C is a global pathogen that causes morbidity and mortality throughout the world. Its seroprevalence is said to have increased over the past 15 years, with about 185 million individuals presently infected. Hepatitis C's health effects are not limited to physical morbidity but include psychosocial elements such as quality of life, depression, anxiety, social support, and stigma fear. The decrease in quality of life (QOL) is one of the most coherent results among the many psychosocial health effects of hepatitis C. However, there is still limited proof of modifiable variables that may boost QOL. It has been shown that resilience–a relatively new concept –is strongly connected with QOL and have multiple beneficial health results. Defined as the capacity to preserve or recover mental health despite experiencing adversity, this structure among patients with hepatitis C has not been properly researched. More specifically, its connection with QOL among patients with hepatitis C has not undergone any empirical testing in the Malaysian context and beyond. This research examined the association between resilience and QOL among patients with hepatitis C attending a tertiary hospital in the state of Pahang, employed a cross-sectional design. A total of 195 patients were recruited through convenience sampling at Hospital Tengku Ampuan Afzan (HTAA), Kuantan. The age of the participants ranged from 21 to 76 years old. The mean age of the participants was 45.6 ± 9.70 years old. Majority of the participants were male (83.1%) with a sex ratio of 5:1 (male to female). Subjects were predominantly Malay (90.3%) and Muslim (90.3%). Among the non-Malay, they were Chinese (7.2%), Indian (2.1%), and others (0.5%). Most of the participants contracted hepatitis C via intravenous drug and 60% of them were on a recovery program. Resilience was evaluated using the validated Connor-Davidson resilience scale, while the validated 36-item short-form survey (SF-36v2) was used to measure Health-Related Quality of Life (HRQOL). Statistical analyses were done using IBM SPSS version 21.0. Health-Related Quality of life gave two component summary score, physical health (PCS) with mean 48.88 ± 8.9; and mental health (MCS) with mean 47.70 ± 9.1, meanwhile, resilience gave mean of 73.27 ± 13.7. Research results indicate that, except for vitality and body pain, all areas with HRQOL of physical and mental health outcome for patients with Pahang hepatitis C are below standard (50). This shows that physical, mental and social health of hepatitis C patient in Pahang is comparatively poor. Multivariate linear regression analyses revealed a strong positive impact of resilience on both PCS and MCS (p <0.05). These findings are expected to help policymakers develop HRQOL projects among hepatitis C patients and to provide feedback to healthcare providers to improve service and care quality. Keywords: Resilience; health-related quality of life (HRQOL); hepatitis C.